2016
DOI: 10.1136/bmj.i6270
|View full text |Cite
|
Sign up to set email alerts
|

Gotta catch’em all! Pokémon GO and physical activity among young adults: difference in differences study

Abstract: Objective To estimate the effect of playing Pokémon GO on the number of steps taken daily up to six weeks after installation of the game.Design Cohort study using online survey data.Participants Survey participants of Amazon Mechanical Turk (n=1182) residing in the United States, aged 18 to 35 years and using iPhone 6 series smartphones.Main outcome measures Number of daily steps taken each of the four weeks before and six weeks after installation of Pokémon GO, automatically recorded in the “Health” applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
153
4
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(183 citation statements)
references
References 15 publications
15
153
4
11
Order By: Relevance
“…Like the AVGs, ARGs allow gamers to replace sedentary screen time with active gameplay and show promising potential for promoting health. Although research exploring the effects of ARGs on physical activity is limited, a recent study by Howe et al [22] suggests that changes in physical activity as a result of playing Pokémon GO are moderate and not sustained. However, these findings have yet to be corroborated by other studies and are specific to Pokémon GO.…”
Section: Exergamingmentioning
confidence: 99%
“…Like the AVGs, ARGs allow gamers to replace sedentary screen time with active gameplay and show promising potential for promoting health. Although research exploring the effects of ARGs on physical activity is limited, a recent study by Howe et al [22] suggests that changes in physical activity as a result of playing Pokémon GO are moderate and not sustained. However, these findings have yet to be corroborated by other studies and are specific to Pokémon GO.…”
Section: Exergamingmentioning
confidence: 99%
“…Overall, these findings suggest that the impact of Pokémon GO on increasing physical activity is short lived. An excitement was noticed in some people with the release of Pokémon GO, which led to a moderate increase in physical activity level (about 11 minutes of additional walking daily); however, this increase in daily steps taken declined gradually over time and was no longer observed after only 6 weeks after installment of the game (15). Based on this well-designed and robust study, Pokémon GO may well be closer to snake oil than a panacea.…”
mentioning
confidence: 85%
“…Many months have now elapsed since the release of Pokémon GO by Niantic, and studies are now starting to get published on the efficacy of this game as a tool to increase physical activity (and hopefully also reducing the associated health risks). One such study by Howe and colleagues was recently published in the British Medical Journal (15). This elegant and timely study aimed at estimating the effect of Pokémon GO on the number of steps taken daily up to 6 weeks after installation of the game.…”
mentioning
confidence: 99%
“…People who play the game actively will most likely spend more time outside, reducing exposure to indoor air pollutants and increasing the benefits of fresh air and sunlight. For instance, Kogan et al [46] have recently found that playing the Pokémon Go helps players to reduce their anxiety Page 1906 about leaving the house, interacting with stranger and visiting new places and concluded that it could be a new opportunity to enhance both mental and physical health. In terms of social wellness, gym battles favor cooperation and lure modules attract other players, both enabling players with shared values to interact and build relationships.…”
Section: Pokémon Go and Wellnessmentioning
confidence: 99%